THE NETWORK OF CARE FOR PEOPLE WITH DISABILITIES IN THE AMAZON: CHALLENGES AND PERSPECTIVES FOR THE IMPLEMENTATION OF SPECIALIZED REHABILITATION CENTERS (CERS) - Sena, Magno Caroline Brum; Nogueira, Julio Muniz; de Oliveira, Bruna Michele; Montes, João Paulo da Conceição; Silva, Cind Micahela Souza; Lima, Anne Mikaele Pantoja Coutinho; Trindade, Cristine dos Santos (Seven Editora, 2025)
This article analyzes the importance of Specialized Rehabilitation Centers (CERs) in promoting comprehensive care for people with disabilities in the Northern Region of Brazil, with a focus on the state of Amazonas. Based on a qualitative, descriptive, and documentary approach, the study used secondary data from official sources and scientific literature published between 2020 and 2024. The results reveal structural and geographical inequalities that limit access to rehabilitation services in the region, especially in remote riverside, Indigenous, and rural communities. Barriers such as the concentration of CERs in capital cities, the shortage of specialized health professionals, and the lack of adequate transportation aggravate the exclusion of vulnerable populations. The discussion highlights the urgent need to expand and decentralize CERs through strategies that respect the territorial specificities of the Amazon and adhere to the principles of equity, regionalization, and comprehensiveness of the Brazilian Unified Health System (SUS). It is concluded that implementing new CERs in the region is not merely a managerial issue, but a matter of social justice and the guarantee of fundamental rights. DOI: https://doi.org/10.56238/sevened2025.029-119